2003
DOI: 10.1046/j.1471-4159.2003.02137.x
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine produces neuronal inclusions in the nigrostriatal system and in PC12 cells

Abstract: Mice treated with the psychostimulant methamphetamine (MA) showed the appearance of intracellular inclusions in the nucleus of medium sized striatal neurones and cytoplasm of neurones of the substantia nigra pars compacta but not in the frontal cortex. All inclusions contained ubiquitin, the ubiquitin activating enzyme (E1), the ubiquitin protein ligase (E3-like, parkin), low and high molecular weight heat shock proteins (HSP 40 and HSP 70). Inclusions found in nigral neurones stained for a-synuclein, a protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
147
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(166 citation statements)
references
References 38 publications
(72 reference statements)
18
147
1
Order By: Relevance
“…METH-induced neurotoxicity in monoaminergic systems has been observed in rats given single large doses (in the range of 20-100 mg/kg) (Cappon et al, 2000;Fukumura et al, 1998;Imam and Ali, 2001;Seiden and Vosmer, 1984) or 5-10 mg/kg, given four times at intervals of 2 h (Chapman et al, 2001). Toxicity in dopaminergic systems was also reported in mice given either a single dose of METH (25 mg/kg) (Hayashi et al, 2001) or multiple doses, with the animals receiving four injections of METH varying from 5 to 10 mg/kg at 2-h intervals (Ali et al, 1994;Fornai et al, 2004;Thomas et al, 2004). Recently, in vivo studies have suggested that METH can also cause neuronal apoptosis in rodents by the concurrent activation of mitochondrial and endoplasmic reticulum death pathways in mice striatal cells (Jayanthi et al, 2004), and by the upregulation of Fas ligand/Fas death pathway in rat striatal cells (Jayanthi et al, 2005).…”
Section: Introductionmentioning
confidence: 92%
“…METH-induced neurotoxicity in monoaminergic systems has been observed in rats given single large doses (in the range of 20-100 mg/kg) (Cappon et al, 2000;Fukumura et al, 1998;Imam and Ali, 2001;Seiden and Vosmer, 1984) or 5-10 mg/kg, given four times at intervals of 2 h (Chapman et al, 2001). Toxicity in dopaminergic systems was also reported in mice given either a single dose of METH (25 mg/kg) (Hayashi et al, 2001) or multiple doses, with the animals receiving four injections of METH varying from 5 to 10 mg/kg at 2-h intervals (Ali et al, 1994;Fornai et al, 2004;Thomas et al, 2004). Recently, in vivo studies have suggested that METH can also cause neuronal apoptosis in rodents by the concurrent activation of mitochondrial and endoplasmic reticulum death pathways in mice striatal cells (Jayanthi et al, 2004), and by the upregulation of Fas ligand/Fas death pathway in rat striatal cells (Jayanthi et al, 2005).…”
Section: Introductionmentioning
confidence: 92%
“…1) even after repeated injections (11,12). Besides MPTP, at least three other toxins, rotenone (13)(14)(15), ubiquitin-proteasome inhibitors (16,17), and methamphetamine (18), produce a PD-like syndrome in mice, but unlike MPTP, these toxins also cause formation of ␣-synuclein-containing inclusions (13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…GFAP staining is considered to be a hallmark of neurotoxicity and has been closely associated with METH or MDMA-induced striatal dopaminergic neurotoxicity (Fornai et al, 2004;Busceti et al, 2008;Granado et al, 2011b;Ares-Santos et al, 2012). Genetic inactivation of dopamine D1 or D2 receptors prevents astrogliosis and provides protection against the neurotoxic effects of METH (Granado et al, 2011a;Ares-Santos et al, 2012).…”
Section: Discussionmentioning
confidence: 99%